Modelo de plan estratégico para modificar la cultura organizacional de la Universidad Nacional de Tumbes - 2011 - Tang Serquén, Isabel Cristina (2012)
The current research study, whose main objective is the proposal of a strategic plan model focused on changing the Organizational Culture of National University of Tumbes, aims to address the need to formulate a viable alternative, which contributes to the achievement of its institutional objectives towards the accreditation. In order to meet the proposed objective, we have sampled the population of employees: professor and administrative staff of the National University of Tumbes, using the survey technique, and as instrumental means, a questionnaire, designed on the basis of the objectives of the research. The tabulation and consequent analysis of the results reflect the perception of the Organizational Culture of the National University of Tumbes, on the side of its workers as inadequate, and therefore capable of being enhanced and improved through intervention of planning. The way to achieve the objectives that this study traces is set through the proposal of a model of participatory strategic plan, involving members of the university community and its interest groups, taking into account the incorporation of strategies for the cultural change .